2021
DOI: 10.1002/jca.21936
|View full text |Cite
|
Sign up to set email alerts
|

Membrane‐based therapeutic plasma exchange: Hemodynamics and operational characteristics leading to procedure failure

Abstract: Background and Objectives: Therapeutic plasma exchange (TPE) is a blood purification treatment capable of removing large molecular weight substances from plasma. It is commonly used for the removal of circulating pathogenic immunoglobulins presumed to be the cause of many autoimmune diseases. TPE can be performed with a membrane-based system (mTPE) or a centrifugal-based system (cTPE). When plasma separation is performed with a membrane, filter clotting can lead to longer treatment time, higher cost and can ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 8 publications
1
5
0
Order By: Relevance
“…In patients that received both prefilter heparin and saline solution, we observed a filter failure rate of 5.2%. This is in comparison to our prior experience where we noted 17.7% filter failure during which 80% of treatments used prefilter heparin (either bolus or infusion) without the use of prefilter saline infusion [7]. A previous study by Gashti et al reported a filter failure of 7.7% in 998 treatment sessions of which only 3.4% received some form of intratreatment anticoagulation [13].…”
Section: Discussionsupporting
confidence: 45%
See 1 more Smart Citation
“…In patients that received both prefilter heparin and saline solution, we observed a filter failure rate of 5.2%. This is in comparison to our prior experience where we noted 17.7% filter failure during which 80% of treatments used prefilter heparin (either bolus or infusion) without the use of prefilter saline infusion [7]. A previous study by Gashti et al reported a filter failure of 7.7% in 998 treatment sessions of which only 3.4% received some form of intratreatment anticoagulation [13].…”
Section: Discussionsupporting
confidence: 45%
“…Currently, with pump driven continuous veno‐venous hemofiltration, the predilution mode remains useful as a means of decreasing the tendency for filter clotting [6]. Given the proven benefits of predilution during CRRT, and the high rate of filter failure previously encountered (17.7%) [7], we initiated a protocol for predilution during mTPE in an attempt to reduce the risk of filter failure.…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies have demonstrated a therapeutic plasma exchange filter failure rate (FFR) ranging from 7.7% to 17.7%. 10,11 As we previously demonstrated, pre-filter normal saline administration does not affect the efficiency of IgG removal. 9 The purpose of this study was to examine the effect of pre-filter heparin and saline on the FFR.…”
Section: Discussionmentioning
confidence: 82%
“…Calcium supplementation was only used in early treatment cases when using 5% albumin replacement solution as we observed a tendency toward filter failure in subgroup analysis when using higher calcium doses without a significant change in post-treatment ionized calcium levels. 11 It was postulated that at physiological steady state 45%-55% of calcium is bound to albumin in the blood, yet an earlier study by Hester et al, demonstrated that by using 5% albumin solution that fraction can increase up to 86%-90%. 12 It was also described that calcium ionization is inversely proportional to pH, and at pH of 6.5 up to 80% of ionized calcium is available, which can decrease to around 40% at a pH of 8.0.…”
Section: Discussionmentioning
confidence: 99%
“…Therapeutic plasma exchange is a plasma purification treatment capable of eliminating large molecular weight substances from blood ( 101 ). It is the fastest way to remove circulating autoantibodies.…”
Section: Therapy Strategies Of Diseases Associated With Anti-ifn Absmentioning
confidence: 99%